Non-24-Hour Sleep-Wake Disorder Revisited – A Case Study - Garbazza, Corrado; Bromundt, Vivien; Eckert, Anne; Brunner, Daniel P.; Meier, Fides; Hackethal, Sandra; Cajochen, Christian (Frontiers in Neurology, 2016)
The human sleep-wake cycle is governed by two major factors: a homeostatic hourglass process (process S), which rises linearly during the day, and a circadian process C, which determines the timing of sleep in an approximately 24h rhythm in accordance to the external light-dark (LD) cycle. While both individual processes are fairly well characterized, the exact nature of their interaction remains unclear. The circadian rhythm is generated by the subthalamic nucleus (SCN, “master clock”) of the anterior hypothalamus, through cell-autonomous feedback loops of DNA transcription and translation. While the phase length (tau) of the cycle is relatively stable and genetically determined, the phase of the clock is reset by external stimuli (“zeitgebers”), the most important being the LD-cycle. Misalignments of the internal rhythm with the LD-cycle can lead to various somatic complaints and ultimately to the development of circadian rhythm sleep disorders (CRSD). Non-24-h sleep-wake disorders (N24HSWD) is a CRSD affecting up to 50% of totally blind patients and characterized by the inability to maintain a stable entrainment of the typically long circadian rhythm (tau >24.5h) to the LD- cycle. The disease is rare (<1:1 Mio) in sighted individuals and the pathophysiology less well understood. Here we present the case of a 40 year old sighted male, who developed a misalignment of the internal clock with the external light-dark cycle following the treatment for Hodgkin’s lymphoma (ABVD regimen, 4 cycles and AVD regimen, 4 cycles). A thorough clinical assessment including actigraphy, melatonin profiles, polysomnography and wake-EEG lead to the diagnosis of a non-24-h sleep-wake disorders (N24HSWD) with a free-running rhythm of tau=25.5h. A therapeutic intervention with bright-light therapy (BLT, 30 min 10.000lux) in the morning and melatonin administration (0.5-0.75 mg) in the evening failed to entrain the free-running rhythm, although a longer treatment duration and more intense therapy might have been successful. The sudden onset and close timely connection led us to hypothesize that the chemotherapy might have caused a mutation of the molecular clock components leading to the observed elongation of the circadian period.